(untitled) (Revista de Ciências Agroveterinárias, 2002)
Radial Immunodiffusion (RID) is the most widely used diagnostic method for sheep brucellosis due to Brucella ovis. It is also used for the diagnosis of canine brucellosis caused by Brucella canis. Antigens used for RID are not standardized and it is possible that reagents from different sources may produce discrepancies, even if the same bacterial strain is used to produce the antigens. Antigens produced by two laboratories (antigens I, IIa and IIb) were compared to an antigen produced following the techniques recommended by FAO/WHO, and considered as standard for the purposes of this study. Antigens were compared by PAGE analysis and RID, and protein concentration determined by the SENSIPROT technique. It was found that one antigen produced two precipitation lines in RID. The same product showed a different pattern of bands in PAGE, with an extra band of protein at 200 KDa. The same antigen had higher protein concentration than the standard and the other antigens.